УДОСКОНАЛЕННЯ СИСТЕМИ АДМІНІСТРАТИВНИХ СТЯГНЕНЬ ЗА ВЧИНЕННЯ АДМІНІСТРАТИВНИХ ПРАВОПОРУШЕНЬ У СФЕРІ ЕКОЛОГІЇ - Прудник, Сергій Володимирович (SUPREMANCE OF LAW, 2017)
The article analyzes the current state of the application the administrative penalties for administrative offenses in the sphere of ecology, the formation of proposals to improve the system in order to increase the effectiveness of administrative responsibility as a means of ensuring the environmental security. It is proved the ineffectiveness of certain type of administrative penalties, which are confirmed by the results of the survey and the analysis of the court decisions. The author says that the issues of improving the system of administrative penalties in the environmental sphere are explained in two problems: firstly, the need for recognition as subjects of administrative responsibility the legal entities, which certainly prove the introducing them to special types of penalties; secondly, unfavorable legal consequences of penalties for socially dangerous consequences caused by committing administrative offenses